2014
DOI: 10.3892/ol.2014.1843
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA expression signatures of bladder cancer revealed by microarray

Abstract: Dysregulation of long noncoding RNAs (lncRNAs) has been regarded as a primary feature of several human cancers. However, the genome-wide expression and functional significance of lncRNAs in bladder cancer remains unclear. The aim of this study was to identify aberrantly expressed lncRNAs that may play an important role in contributing to bladder cancer pathogenesis. In this study, we described lncRNAs profiles in four pairs of human bladder cancer and matched normal bladder tissues by microarray. We finally de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…Our result support Zhu et al' finding [19]. The annotation results of the most significant Gene Ontology items were cellular metabolic process, poly(A) RNA binding, immune system process, immune response and receptor binding, indicating related coding gene contribute to development of BC.…”
Section: Discussionsupporting
confidence: 90%
“…Our result support Zhu et al' finding [19]. The annotation results of the most significant Gene Ontology items were cellular metabolic process, poly(A) RNA binding, immune system process, immune response and receptor binding, indicating related coding gene contribute to development of BC.…”
Section: Discussionsupporting
confidence: 90%
“…Cancer cells adopt various strategies to override apoptosis, including the upregulation of anti-apoptotic machinery, the down regulation of pro-apoptotic factors or a combination of these strategies (37). A number ofcancer-associated lncRNAs have been identified that affect apoptosis via various pathways (10,38,39). The most prominent pathways for apoptosis are activated by the mitochondria or death receptors from the tumor necrosis factor (TNF) family through various cascade reactions (40).…”
Section: Discussionmentioning
confidence: 99%
“…Two studies showed that expression levels of multiple, bladder cancer-specific lncRNAs correlated with expression of protein-coding genes involved in the p53 signalling pathway, mTOR signalling or in cell cycle regulation [18, 25]. Peter et al .…”
Section: Discussionmentioning
confidence: 99%